2017
DOI: 10.1111/adb.12539
|View full text |Cite
|
Sign up to set email alerts
|

Chronic ethanol consumption: role of TLR3/TRIF‐dependent signaling

Abstract: Chronic ethanol consumption stimulates neuroimmune signaling in the brain, and Toll-like receptor (TLR) activation plays a key role in ethanol-induced inflammation. However, it is unknown which of the TLR signaling pathways, the myeloid differentiation primary response gene 88 (MyD88) dependent or the TIR-domain-containing adapter-inducing interferon-β (TRIF) dependent, is activated in response to chronic ethanol. We used voluntary (every-other-day) chronic ethanol consumption in adult C57BL/6J mice and measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 54 publications
1
53
0
2
Order By: Relevance
“…It is important to note that the genomic effects of alcohol consumption vary based on ethanol exposure model, duration, and time following exposure (McCarthy et al, 2017; Osterndorff-Kahanek et al, 2013; 2015; Whitman et al, 2013). Thus, the results from this study present a single snapshot of how alcohol impacts the microglial transcriptome.…”
Section: 4 Conclusionmentioning
confidence: 99%
“…It is important to note that the genomic effects of alcohol consumption vary based on ethanol exposure model, duration, and time following exposure (McCarthy et al, 2017; Osterndorff-Kahanek et al, 2013; 2015; Whitman et al, 2013). Thus, the results from this study present a single snapshot of how alcohol impacts the microglial transcriptome.…”
Section: 4 Conclusionmentioning
confidence: 99%
“…The potential clinical relevance of the interaction between the effects of AUD on the immune system and the possible role of this latter in regulating drinking has received further in vivo validation with the observation that TLR3-TIR-domain-containing adapter-inducing interferon-β (TRIF) pathway are activated during chronic ethanol consumption. The IKKε/TBK1 inhibitor Amlexanox down-regulates TRIF-dependent pathway in the brain and reduces ethanol consumption, suggesting that the TRIF-dependent pathway is implicated in regulation of drinking (26). Hence, the NFKB pathway that lies downstream the activation of TLR signaling may also play a non canonical non-immune role in mediating complex behaviors, including processes of learning and memory, stress responses, anhedonia and drug reward (27).…”
Section: Introductionmentioning
confidence: 99%
“…Acute and chronic ethanol exposure induce an innate immune response in the central nervous system (CNS) of humans, and this effect is replicated in preclinical models of alcohol use disorder (AUD) [1][2][3][4]. Most notably, genomic studies in mice [5], rats [6], and humans [3,7,8] have identified several members of the Toll-like receptors (TLR) and interleukin-1/interleukin18 (IL-1/IL-18) receptor pathways in AUD [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Most notably, genomic studies in mice [5], rats [6], and humans [3,7,8] have identified several members of the Toll-like receptors (TLR) and interleukin-1/interleukin18 (IL-1/IL-18) receptor pathways in AUD [9,10]. Moreover, pharmacological [11][12][13], viral [14,15], or transgenic [2,9,11,[16][17][18][19][20] manipulation of the innate immune system leads to alterations of the ethanol-related behaviors in rodents. Collectively, this growing literature on innate immune responses critically contributing to the neurobiology of AUD [21][22][23] suggests that these pathways have high potential as targets for the development of new AUD therapeutic strategies [16,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%